INCREASING INTEREST IN LEARNING THE HISTORY OF ISLAMIC CULTURE USING AUDIO-VISUAL MEDIA - Nikmatul Musayadah; Asripa; Aliyah; Robiatul Adawiyah (International Journal of Multidisciplinary Reseach, 2025)
Learning media, which is one of the learning components, has an important role in teaching and learning activities (KBM). Through learning media, teachers can increase students' interest in learning so that learning objectives can be achieved effectively. Using audio visual media requires an active role from the teacher so that the use of this media can provide many benefits in the learning process, so in this research the author discusses students' interest in learning in SKI lessons through audio visuals at MTs. Alawiyah. The research design used is Classroom Action Research (PTK) which aims to increase student interest in learning for class IX MTs Alawiyah students. After taking action in cycle II, it began to show that some students were starting to become interested. We can see that the percentage of success reached 80% and 20% of failure, resulting in an increased percentage as expected, in cycle I 40%, cycle II 80%.